(untitled) (Journal of Contemporary Philology, 2018)
This paper delves into the English translation of one of the most renowned Macedonian poet and novelist –Petre M. Andreevski. It analyses the translations of two poems, the anthological Making Love to Deniciaand This Side and Beyond; followed by interpretations of the different semantic nuances between the original and the translation (versification). For this purpose, Dragi Mihajlovski’s method known as ‘map of deviation’ is being used in order to present the deviations on a phonological, lexical, syntactic and semantic level. Each linguistic estrangement is discussed in details and new translation equivalents are offered and justified. The aim is to emphasizethe creative process of translation and the never-ending struggle of the translator, especially in poetry translation. The paper revolves around the translation of the metaphysical elements in some of Andreevski’s poems. In search of better translation equivalents, a new translation of the poems at hand is encompassed towards the end of the paper. The new translation is an attempt to reach the aesthetic equivalent of the original and to translate the untranslatable in poetry